Experiments in political science: Contributions and challenges to the discipline - Alfaro Redondo, Ronald (2015)
In this review article I describe the advantages of experimental research in political science and summarize the state-of-the-art in the literature that postulates that their proliferation is mainly because experiments are superior to all other methods in disentangling cause and effect relationships. Experiments have proven to be versatile enough to accommodate into researchers’ preferences, complex research questions and innovative designs. We have witnessed the expansion of methods, the advance in theory testing, and the improvement in establishing causal relationships that experiments have brought to political science. Also, I provide some examples of experiments in the literature that expanded our knowledge. In the last section I offer an overview of the limitations of experimental design.